Dermoscopic Features and Their Diagnostic Values Among Common Inflammatory and Infectious Dermatoses: A Cross-Sectional Study - Pakornphadungsit K; Suchonwanit P; Thadanipon K; Visessiri Y; Rutnin S (Dove Medical Press, 2023)
Kallapan Pakornphadungsit,1 Poonkiat Suchonwanit,1 Kunlawat Thadanipon,2 Yingluck Visessiri,3 Suthinee Rutnin1 1Division of Dermatology, Department of Internal Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Clinical Epidemiology and Biostatistics, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Suthinee Rutnin, Division of Dermatology, Department of Internal Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, Thailand, 10400, Tel +66-2-2011141, Fax +66-2-201-1211 ext 4, Email suthinee.rutnin@gmail.comBackground: Dermoscopy is a non-invasive tool widely used to improve the diagnostic accuracy of general dermatological conditions.Objective: To determine the dermoscopic features and their diagnostic value in distinguishing common inflammatory and infectious dermatoses.Materials and Methods: A cross-sectional study was conducted on patients clinically diagnosed with common inflammatory or infectious skin diseases. Baseline characteristics and clinical and dermoscopic findings were recorded. Dermoscopic variables were analyzed using a correlation matrix. A skin biopsy was performed for each patient for a definitive diagnosis.Results: Of 102 patients, 43 with dermatitis, 30 with psoriasis, 14 with lichen planus (LP), 5 with pityriasis rosea (PR), and 10 with others were included. Dull red background, patchy vessels, and scales showed significant positive correlations with dermatitis (r = 0.401, 0.488, and 0.327, respectively; p < 0.01), whereas bright red background, glomerular vessels, regular vascular distribution, and diffuse scales revealed significant positive correlations with psoriasis (r = 0.412, 0.266, 0.798, and 0.401, respectively; p < 0.01). For LP, whitish reticulate structures, purplish background, and dotted vessels mixed with linear vessels in the peripheral distribution were significantly positively correlated (r = 0.831, 0.771, 0.224, and 0.558, respectively; p < 0.05). Yellowish background and peripheral scales were predictive of PR diagnosis (r = 0.254 and 0.583, respectively; p < 0.01).Conclusion: Dermoscopy can be used as an adjunctive tool to differentiate conditions among common inflammatory and infectious dermatoses in order to minimize unnecessary invasive diagnostic procedures.Keywords: dermoscopy, dermoscopic finding, inflammatory skin disease, infectious skin disease, papulosquamous disease